Advances in cathode designs and reactor configurations of microbial electrosynthesis systems to facilitate gas electro-fermentation - Bajracharya, Suman; Krige, Adolf; Matsakas, Leonidas; Rova, Ulrika; Christakopoulos, Paul (Bioresource technology, 2022)
[Display omitted] •MES integration with gas fermentation is promising to sustain bioproduction.•Various cathode materials and their performances in MES are reviewed.•Different aspects of effective cathode and reactor design are explored.•Strategies are offered for future research on gas electro-fermentation in MES. In gas fermentation, a range of chemolithoautotrophs fix single-carbon (C1) gases (CO2 and CO) when H2 or other reductants are available. Microbial electrosynthesis (MES) enables CO2 reduction by generating H2 or reducing equivalents with the sole input of renewable electricity. A combined approach as gas electro-fermentation is attractive for the sustainable production of biofuels and biochemicals utilizing C1 gases. Various platform compounds such as acetate, butyrate, caproate, ethanol, butanol and bioplastics can be produced. However, technological challenges pertaining to the microbe-material interactions such as poor gas–liquid mass transfer, low biomass and biofilm coverage on cathode, low productivities still exist. We are presenting a review on latest developments in MES focusing on the configuration and design of cathodes that can address the challenges and support the gas electro-fermentation. Overall, the opportunities for advancing CO and CO2-based biochemicals and biofuels production in MES with suitable cathode/reactor design are prospected.